Binding site of different tannins on a human salivary proline-rich protein evidenced by dissociative photoionization tandem mass spectrometry. Issue 20 (20th May 2015) - Canon, Francis; Ployon, Sarah; Mazauric, Jean-Paul; Sarni-Manchado, Pascale; Réfrégiers, Matthieu; Giuliani, Alexandre; Cheynier, Véronique
Abstract: The sensation of astringency is thought to originate from the interaction occurring between tannins and the salivary proline-rich proteins (PRPs). Astringency perception can be modified by the structure of tannins. Herein, we study the interactions occurring between the human salivary PRP, IB5, and three model tannins with different structure, epigallocatechin gallate and the procyanidin dimers B2 and B2 3′ O -gallate, using the coupling of mass spectrometry and VUV-synchrotron radiation. The results obtained indicate that the structure of tannins, in particular the degree of polymerization and the galloylation, does not modify the binding site on IB5 involved in the interaction. Graphical abstract: